Characterization and activity of endophytic bacteria from ‘Prata Anã’ banana crop (Musa sp., AAB) - Gomes Silva Pereira, Débora Francine; Nietsche, Silvia; Aparecida Xavier, Adelica; de Souza, Suzane Ariádina; Costa, Márcia Regina; Barbosa Duarte, Anunciene (Revista Ceres, 2025)
The objective of this study was to characterize banana tree endophytic bacteria at genus and species level and to determine the metabolic reactions associated with the nitrogen transformations. The identification at genus and species levels was performed using the partial sequencing of the rDNA 16S region. The assimbyotic nitrogen fixation, the reduction of nitrate and the production of urease were in vitro evaluated. The DNA of the bacterial isolates was also amplified to verify the presence of the nifH, nirK and nirS regions. Biochemical tests were performed in a complete randomized design; the treatments consisted of 39 bacterial isolates with three replications. Sequence analysis enabled the identification of four genera: Bacillus, Rhizobium, Klebsiella and Enterobacter. The Bacillus genus occurred more frequently, nine species were identified. By evaluating the results of biochemical tests, it was observed that three isolates showed multiple abilities: growth in NFb medium, nitrate reduction and production of urease. The isolates belong to the genus Bacillus and of the species subtilis, thuringienses and amyloliquefaciens. Approximately 12.5% of the isolates amplified the region corresponding to the nifH gene, 7.5% amplified gene nirK and 3.9% amplified the nirS gene. Endophytic bacteria evaluated in the present study showed in vitro activity for urease, nitrate reductase enzymes, however, relevant nitrogenase activity was not observed.